2015
DOI: 10.1111/imb.12164
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 CYP4DE1 and CYP6CW3v2 contribute to ethiprole resistance inLaodelphax striatellus(Fallén)

Abstract: Laodelphax striatellus Fallén (Hemiptera: Delphacidae), a destructive pest of rice, has developed high resistance to multiple insecticides, threatening the success of pest management programmes. The present study investigated ethiprole resistance mechanisms in a field population that is highly resistant to ethiprole. That population was used to establish a laboratory population that was subjected to further selection to produce a resistant strain. Target genes were cloned and compared between the resistant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…RNAi‐based technology has shown great potential in controlling insect pests by silencing their vital genes (Baum et al ., ; Mao et al ., ). RNAi has also been successfully used to investigate the function of P450s in many insect species (Zhang et al ., ; Elzaki et al ., ; Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…RNAi‐based technology has shown great potential in controlling insect pests by silencing their vital genes (Baum et al ., ; Mao et al ., ). RNAi has also been successfully used to investigate the function of P450s in many insect species (Zhang et al ., ; Elzaki et al ., ; Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Based on previous studies monitoring insecticide resistance during 2014 and 2015 in our lab, BPH had developed high levels of resistance to ethiprole and moderate levels to butene‐fipronil in some areas of China (data not shown), which were possibly explained by the cross‐resistance among the phenylpyrazoles used intensively and extensively in immigrant source countries such as Thailand. However, for SBPH, it was reported that the ethiprole resistance mechanism was related to cytochrome P450 CYP4DE1 and CYP6CW3v2, and the A2′N mutation also existed in the laboratory ethiprole‐resistant strain (resistance ratio 180‐fold) . In our study, according to the survey, the three field populations tested were previously exposed to ethiprole at different frequencies.…”
Section: Discussionmentioning
confidence: 81%
“…Generally, SBPH is mainly distributed in temperate and subtropical regions from about 30° N in East Asia, and pest management has depended heavily on synthetic insecticides . However, a few cases of high‐level resistance (>100‐fold) to various insecticides in field populations of SBPH, including neonicotinoids (imidacloprid), organophosphates (chlorpyrifos), carbamates (propoxur), phenylpyrazoles (ethiprole and fipronil) and other pesticides with novel modes of action (such as buprofezin), have been reported in China and Japan, which show that the scientific and rational application of pesticides should be considered in SBPH control so as to delay the development of insecticide resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The ethiprole‐resistant strain of L. striatellus with 107‐fold resistance to ethiprole originated from a paddy field in May 2013 in Ji'ning City, Shandong Province, China. Subsequently, the ethiprole‐resistant strain was derived by continuous selection for 14 generations using a dose of insecticide equal to the median lethal dose (LD 50 ) of their parents and the high‐ethiprole‐resistant (> 5000‐fold) strain, which was used in the present study, was sprayed with successively higher concentrations of ethiprole to maintain and develop its resistance. Susceptible and ethiprole‐resistant strains of L. striatellus were maintained in the laboratory and reared on rice plants ( Oryza sativa L.…”
Section: Methodsmentioning
confidence: 99%